Full-Length Transcriptome Analysis Provides New Insights Into the Diversity of Immune-Related Genes in Portunus trituberculatus - Zhang, Yi; Ni, Mengqi; Bai, Yunhui; Shi, Qiao; Zheng, Jinbin; Cui, Zhaoxia (Frontiers in Immunology, 2022)
Generally, invertebrates were thought to solely rely on their non-specific innate immune system to fight against invading microorganisms. However, increasing studies have implied that the innate immune response of invertebrates displayed diversity and specificity owing to the hyper-variable immune molecules in organisms. In order to get an insight into the diversity of immune-related genes in Portunus trituberculatus, a full-length transcriptome analysis of several immune-related tissues (hemocytes, hepatopancreas and gills) in P. trituberculatus was performed and the diversity of several immune-related genes was analyzed. The full-length transcriptome analysis of P. trituberculatus was conducted using a combination of SMRT long-read sequencing and Illumina short-read sequencing. A total of 17,433 nonredundant full-length transcripts with average length of 2,271 bp and N50 length of 2,841 bp were obtained, among which 13,978 (80.18%) transcripts were annotated. Moreover, numerous transcript variants of various immune-related genes were identified, including pattern recognition receptors, antimicrobial peptides, heat shock proteins (HSPs), antioxidant enzymes and vital molecules in prophenoloxidase (proPO)-activating system. Based on the full-length transcriptome analysis, open reading frames (ORFs) of four C-type lectins (CTLs) were cloned, and tissue distributions showed that the four CTLs were ubiquitously expressed in all the tested tissues, and mainly expressed in hepatopancreas and gills. The transcription of the four CTLs significantly increased in several immune-related tissues (hemocytes, hepatopancreas and gills) of P. trituberculatus challenged with Vibrio alginolyticus and displayed different profiles. Moreover, the four CTLs displayed distinct bacterial binding and antibacterial activities. The recombinant protein PtCTL-1 (rPtCTL-1) and rPtCTL-3 displayed bacterial binding and antibacterial activities against all tested bacteria. rPtCTL-2 only showed bacterial binding and antibacterial activities against V. alginolyticus. No obvious bacterial binding or antibacterial activities for PtCTL-4 was observed against the tested bacteria. This study enriches the transcriptomic information on P. trituberculatus and provides new insights into the innate immune system of crustaceans. Additionally, our study provided candidates of antibiotic agents for the prevention and treatment of bacteriosis.